Degradasi Protein Selama Fermentasi Koro Kratok (Phaseolus lunatus) menggunakan Rhizopus oligosphorus - Marta Handayani; Ira Gusti Riani; Aldilla Sari Utami; Onne Akbar Nur Ichsan (Jurnal Teknologi Agro-Industri, 2023)
Koro kratok fermentation used Rhizopus oligosphorus was one of Indonesian’s society methods to consumed Koro kratok. Rhizopus oligosphorus produced proteolytic enzyme which can be used to break down complex protein to simple protein. Protein degradation was observed based on the fermentation time of koro kratok. Fermentation times used were 0 hours, 12 hours, 24 hours, 36 hours, 48 hours, 72 hours, 96 hours and 120 hours of fermentation. Parameters observed included proteolytic activity, growth of Rhizopus oligosphorus mycelium, dissolved protein, protein concentration and degree of hydrolysis also protein pattern using SDS PAGE. Observation showed that proteolytic activity, Rhizopus oligosphorus mycelium growth, dissolved protein, protein concentration and degree of hydrolysis were directly proportional to the length of fermentation time. The results of observation on protein patterns using SDS PAGE show that the longer the fermentation time, the simpler the protein produced. The longer the fermentation time, the bigger protein degration of koro kratok.